Migrations like any other? Internal migrations of immigrants in the French countryside (2011-2015) - Julie Fromentin (Université des Sciences et Technologies de Lille, 2021)
A well known feature of the demographic renewal of the French countryside is the settlement of international migrants. Surprisingly, therefore, internal migrations of immigrants towards rural areas have been largely understudied. Through the study of census data (INSEE, 2013), this paper brings another perspective to bear on the geography of immigration in France by analysng internal migrations of immigrants in metropolitan France between 2011 and 2015, especially towards rural areas. I show strong evidence that the movement of immigrants has been a key factor in the demographic growth of rural areas, especially through processes of suburbanisation. The results reveal the similarities between immigrant and non-immigrant individuals who migrated to the countryside (in terms of age, family situation and occupational categories); they also highlight several features which are specific to immigrants in some rural areas.